Institutionalizing Ethical Innovation in Organizations: An Integrated Causal Model of Moral Innovation Decision Processes - Schumacher, E. Günter; Wasieleski, David M. (2013)
This article answers several calls—coming as well from corporate governance practitioners as from corporate governance researchers—concerning the possibility of complying simultaneously with requirements of innovation and ethics. Revealing the long-term orientation as the variable which permits us to link the principal goal of organization, being “survival,” with innovation and ethic, the article devises a framework for incorporating ethics into a company’s processes and strategies for innovation. With the principal goal of organizations being “survival” in the long-term, it is assumed that innovation is necessary in order to realize a going concern. Firms that do not innovate and adapt to rapidly changing business environments are less likely to be sustainable. Thus, it is in a business’ best interests to adopt an innovation process for long-term success. We posit that there are two simultaneous sources of innovation and change that are unavoidable and embedded in the corporate landscape. First, we argue for genetically embedded, Darwinian explanations for adaptations that enable an entity’s survival. This view is combined with more conventional, social science explanations for change. Our new, comprehensive model of the governance of innovation processes hinges on the one hand on an organization’s long-term orientation, which we argue, is not possible without a consideration of an ethical dimension. On the other hand, the model employs, for the first time, the concept of duality, in order to make the positive coexistence of innovation and ethic analytically visible. Guided by this concept the roots of the ethic within innovation are traced from both natural science forces for change, and cultural pressures operating on members of an organization. We present our Integrated Causal Model of Innovation and propose theoretical relationships that will generate numerous avenues for future research in the field, and help managers to reorient their governance strategies.
Keywords: Values; Natural Science; Innovation; evolutionary theory; Culture; Corporate Governance; Business Ethics